1996
DOI: 10.1177/016264349601300102
|View full text |Cite
|
Sign up to set email alerts
|

Assistive Technology in Schools: Are Teachers Ready, Able, and Supported?

Abstract: This article summarizes the results of a survey of teachers in Pennsylvania who have educational responsibility for one or more students who use assistive technology in the classroom. The majority of these students had some type of physical disability and used an augmentative communication device. The teachers who responded to this survey were highly educated and experienced in the use of computers and assistive technology. Issues surrounding the complexity of the equipment were among the greatest barriers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 9 publications
3
35
0
1
Order By: Relevance
“…Studies conducted during the past 20 years have documented lack of access to technology, insufficient funding, and the need for further training as the most commonly expressed needs and barriers to AT implementation and use (e.g., Derer, et al, 1996;McGregor & Pachuski, 1996;Milligan, Edmiston, & Jackson, 2013). Results of this study demonstrate the same trends.…”
Section: Barriers and Actions To Improve At Usementioning
confidence: 99%
“…Studies conducted during the past 20 years have documented lack of access to technology, insufficient funding, and the need for further training as the most commonly expressed needs and barriers to AT implementation and use (e.g., Derer, et al, 1996;McGregor & Pachuski, 1996;Milligan, Edmiston, & Jackson, 2013). Results of this study demonstrate the same trends.…”
Section: Barriers and Actions To Improve At Usementioning
confidence: 99%
“…Accordingly, there is a need for systematic information concerning the technical equipment and hearing impairment. Such information improves the teachers' understanding of the need for teaching interventions (Lynas 1986;Antia et al 2009;Punch and Hyde 2010;Chmiliar 2007;McGregor and Pachuski 1996;Wright et al 2006;Craddock 2006), and therefore encourage positive attitudes towards and frequent use of the equipment.…”
Section: The Importance Of Positive Attitudesmentioning
confidence: 99%
“…Advances in technology have increased the inventory of available tools and teaching strategies to improve the participation of children with disabilities in educational settings and activities (McGregor and Pachuski 1996). This technology can be important for inclusive schools which are the guiding political vision in Norway; every child has the right to attend a school in their local community, and all teaching must be adapted to the individual's abilities and interests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies identified that the school community and school facilities are necessary for successful use of innovation among students with visual impairments (Apling & Jones, 2007;Edyburn, 2004;Kelly, 2009;Poel, 2007). Scholars have recognized the critical role of teachers in supporting students using innovation and assistive technology (Lahm & Nickels, 1999;McGregor & Pachuski, 1996;Silberman & Sacks, 2007).…”
Section: Support To Use the Innovationmentioning
confidence: 99%